Profissionalização e acesso ao trabalho para os jovens: elementos sociojurídicos - Lépore, Paulo Eduardo [UNESP] (2014)
This thesis analyzed the social-juridical aspects related to the professionalization and access to employment for young people. The study was based on a historical development of the children, adolescents and youth rights, with emphasis on key documents in the International Law of Human Rights and the Brazilian Law. We attempted to clarify who the young people are and to what extent they appear as subjects of special rights. The service policies and principles stated in the Statute of the Children and Adolescents and in the Statute of the Youth were identified and analyzed. The right of the young ones to professionalization has been studied from a historical perspective articulated with the rights to education and employment protection. We performed a critical analysis of the fundamental rights to education, professional training and to employment taking into account all regulatory sources that permeate them. The public policies idealized for the youth were investigated taking as itspremise the technological evolution that creates the demand for workers with employment, i.e., those individuals who have enough skills to adapt to the changes in the labor market. The social-juridical analysis performed in this study allowed the unveiling of the unconstitutional, illegal or uneven way some social policies are devised and implemented, notably those relating to the professionalization and access to employment. The income transfer programs, such as Bolsa Familia, and the ones of educational incentives, such as PROUNI, PNAES and Ciência Sem Fronteiras, were explored as concrete and promising alternatives of professionalization and access to employment for young people